Mechanosensitive enteric neurons in the guinea pig gastric corpus - Mazzuoli-Weber, Gemma (Front Cell Neurosci, 2015)
For long it was believed that a particular population of enteric neurons, referred to as intrinsic primary afferent neuron (IPAN)s, encodes mechanical stimulation. We recently proposed a new concept suggesting that there are in addition mechanosensitive enteric neurons (MEN) that are multifunctional. Based on firing pattern MEN behaved as rapidly, slowly, or ultra-slowly adapting RAMEN, SAMEN, or USAMEN, respectively. We aimed to validate this concept in the myenteric plexus of the gastric corpus, a region where IPANs were not identified and existence of enteric sensory neurons was even questioned. The gastric corpus is characterized by a particularly dense extrinsic sensory innervation. Neuronal activity was recorded with voltage sensitive dye imaging after deformation of ganglia by compression (intraganglionic volume injection or von Fry hair) or tension (ganglionic stretch). We demonstrated that 27% of the gastric neurons were MEN and responded to intraganglionic volume injection. Of these 73% were RAMEN, 25% SAMEN, and 2% USAMEN with a firing frequency of 1.7 (1.1/2.2), 5.1 (2.2/7.7), and of 5.4 (5.0/15.5) Hz, respectively. The responses were reproducible and stronger with increased stimulus strength. Even after adaptation another deformation evoked spike discharge again suggesting a resetting mode of the mechanoreceptors. All MEN received fast synaptic input. Fifty five percent of all MEN were cholinergic and 45% nitrergic. Responses in some MEN significantly decreased after perfusion of TTX, low Ca(++)/high Mg(++) Krebs solution, capsaicin induced nerve defunctionalization and capsazepine indicating the involvement of TRPV1 expressing extrinsic mechanosensitive nerves. Half of gastric MEN responded to intraganglionic volume injection as well as to ganglionic stretch and 23% responded to stretch only. Tension-sensitive MEN were to a large proportion USAMEN (44%). In summary, we demonstrated for the first time compression and tension-sensitive MEN in the stomach; many of them responded to one stimulus modality only. Their proportions and the basic properties were similar to MEN previously identified by us in other intestinal region and species. Unlike in the intestine, the responsiveness of some gastric MEN is enhanced by extrinsic TRPV1 expressing visceral afferents.